Buddhist Foundations of Mindfulness - Shonin, Edo.; Van Gordon, William; Singh, Nirbhay N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book explores a wide range of mindfulness and meditative practices and traditions across Buddhism. It deepens contemporary understanding of mindfulness by examining its relationship with key Buddhist teachings, such as the Four Noble Truths and the Noble Eight-Fold Path. In addition, the volume explores how traditional mindfulness can be more meaningfully incorporated into current psychological research and clinical practice with individuals and groups (e.g., through the Buddhist Psychological Model). Key topics featured in this volume include: Ethics and mindfulness in Pāli Buddhism and their implications for secular mindfulness-based applications. Mindfulness of emptiness and the emptiness of mindfulness. Buddhist teachings that support the psychological principles in a mindfulness program. A practical contextualization and explanatory framework for mindfulness-based interventions. Mindfulness in an authentic, transformative, everyday Zen practice. Pristine mindfulness. Buddhist Foundations of Mindfulness is an indispensable resource for clinical psychologists, and affiliated medical and mental health professionals, including specialists in complementary and alternative medicine as well as social work as well as teachers of Buddhism and meditation.
Chapter 1. A Buddhist Definition and Operationalization of Mindfulness -- Chapter 2. A Buddhist Psychological Model of Mindfulness -- Chapter 3. The Meanings and Origins of Sati -- Chapter 4. Different Buddhist Perspectives on Mindfulness -- Chapter 5. Understanding and Practicing the Anapanasati Sutra -- Chapter 6. Understanding and Practicing the Satipatthana Sutra -- Chapter 7. Mindfulness and the Four Noble Truths -- Chapter 8. Mindfulness and the Noble Eight-Fold Path -- Chapter 9. Mindfulness and the Three Dharma Seals -- Chapter 10. Mindfulness and Emptiness -- Chapter 11. Mindfulness and the Brahmaviharas -- Chapter 12. Mindfulness and the Six Perfections -- Chapter 13. Mindfulness and the Middle Way -- Chapter 14. Mindfulness and the Nature of Mind -- Chapter 15. Buddhist Foundations of Self-Compassion.
Keywords: Psychology; Complementary medicine; Social work; Clinical psychology; Psychology; Clinical Psychology; Complementary & Alternative Medicine; Social Work; Electronic books